PENANAMAN DISIPLIN MELALUI KEGIATAN UPACARA BENDERA DI TAMAN KANAK-KANAK KEMALA BHAYANGKARI 03 ALAI PADANG - Sukra, Nofriza; Wirman, Asdi (IAIIG Cilacap, 2019)
This research began with the uniqueness of the flag ceremony. This kindergarten has basic principles that emphasize discipline character education. The purpose of this study is to describe implentation discipline through flag ceremony activities. This study uses a qualitative approach with descriptive methods. The informants of this study were teachers and principals. Data collection in this study uses observation, interview, and documentation techniques. The data analysis technique used follows the steps of Miles and Huberman. The technique of validating the data used is a triangulation technique. The results of this study found that disciplinary safeguards through flag ceremony activities in Kemala Bhayangkari 03 Alai Padang Kindergarten were well implemented. Judging from the preparation of the flag ceremony until the flag ceremony is complete. So that it appears that the discipline instilled by teachers includes discipline in marching, dressing, time, and attendance. The teacher performs by direct practice, exemplary, habituation, instruction, dialogue, giving advice, and giving rewards. Constraints faced by teachers such as children are not calm and quickly bored, disciplines of dress still visible there are teachers and children not wearing the same and complete uniforms, time discipline and attendance discipline still seen there are children who are late and ceremony implementers who do not come. How to react, the teacher is consistent with the rules made and creates a role model.